2016
DOI: 10.1371/journal.pone.0154335
|View full text |Cite
|
Sign up to set email alerts
|

Remote Physical Activity Monitoring in Neurological Disease: A Systematic Review

Abstract: ObjectiveTo perform a systematic review of studies using remote physical activity monitoring in neurological diseases, highlighting advances and determining gaps.MethodsStudies were systematically identified in PubMed/MEDLINE, CINAHL and SCOPUS from January 2004 to December 2014 that monitored physical activity for ≥24 hours in adults with neurological diseases. Studies that measured only involuntary motor activity (tremor, seizures), energy expenditure or sleep were excluded. Feasibility, findings, and protoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
135
1
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 170 publications
(150 citation statements)
references
References 169 publications
(329 reference statements)
3
135
1
6
Order By: Relevance
“…This finding replicates previous findings of strong 3 correlations between self-report and accelerometry measures for MS [36]. Studies have shown similar correlations between sensor data streams and functional rating scales for other neurological conditions, suggesting this could be an area for further exploration [16]. In addition, participants with no walking symptoms or disability averaged more than 2,000 steps per day compared to those that experience symptoms but did not have a disability, suggesting that the onset of symptom may be a driver of diminished physical activity.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…This finding replicates previous findings of strong 3 correlations between self-report and accelerometry measures for MS [36]. Studies have shown similar correlations between sensor data streams and functional rating scales for other neurological conditions, suggesting this could be an area for further exploration [16]. In addition, participants with no walking symptoms or disability averaged more than 2,000 steps per day compared to those that experience symptoms but did not have a disability, suggesting that the onset of symptom may be a driver of diminished physical activity.…”
Section: Discussionsupporting
confidence: 89%
“…Daily step count data were collected for all participants. The Fitbit One TM has been shown to be a valid and reliable indicator of step counts [15,16].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…By comparison, there is a substantially smaller, yet steadily increasing body of literature in this area that involves persons with mobility disability such as multiple sclerosis (MS) [2]. This might be explained by the only recent shift in paradigm wherein physical activity is now recognized as yielding beneficial effects on symptoms and function in this population rather than being potentially harmful for MS [3].…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, the evidence presented suggests that multiaxial accelerometer or multisensor devices appear to produce the most valid and reliable data about physical activity in chronic disease populations [14,18,19]. A recent systematic review concluded that remote physical activity monitoring is feasible in individuals with neurological diseases, including those with moderate-to-severe disability [20]. Another recent review which evaluated a range of wearable and non-wearable devices for objectively measuring a range of motor symptoms in Parkinson disease (PD) highlighted that while a number of devices can be recommended, further clinimetric testing and clinical validation are required [21].…”
Section: Introductionmentioning
confidence: 99%